Evaluation of in vitro cytotoxicity and in vivo potential toxicity of the extract from in vitro cultivated Anoectochilus roxburghii Lindl. Issue 24 (17th December 2021) - Chung, Doan Chinh; Long Le, Thanh; Ho, Nguyen Quynh Chi; Nguyen, Thi Thuy; Do, Dang Giap; Do, Duc Thang; Nguyen, Thi Phuong Mai; Nguyen, Thi Phuong Thao; Hoang, Nghia Son
ABSTRACT: Anoectochilus roxburghii Lind. ( A. roxburghii ) has promising anti-oxidant, hyperglycemic, hepatoprotective, and immunomodulatory activities as well as anti-tumor effects. However, the pharmacological actions of in vitro cultured plants remain to be determined. Therefore, the objective of the study was to assess in vitro cytotoxicity and in vivo potential toxicity of an extract derived from in vitro cultivated A. roxburghii, termed as iARE. The total flavonoid content and predominant flavonoid compounds of extract were identified and quantitatively analyzed. The in vitro cytotoxicity of iARE was examined using several cancer and normal cell lines. The apoptotic activity and expression of apoptosis-associated genes were also examined in MCF7 cells to determine the underlying mechanisms related to anti-proliferative effects. In vivo potential toxicity of iARE was assessed following acute and subchronic oral administration in Sprague Dawley rats. Quercetin, kaempferol, and isorhamnetin were three flavonoid components identified in iARE. The extract exerted cytotoxic effects on various cancer cells but not normal fibroblasts. Apoptosis in MCF7 cells was induced by iARE in a concentration-dependent manner associated with increased Bax/Bcl-2 ratio and reduced mitochondrial membrane potential ΔΨm, leading to release of cytochrome c, activation of caspase-3/7 and caspase-9, and cleavage of PARP. In the acute oral toxicity study, no mortality or toxicological signs were observed in rats at 1000 or 5000 mg/kg. In a subchronic oral toxicity study, iARE at a dosage of up to 1000 mg/kg produced no mortality or treatment-related adverse effects on general behavior, food intake, body weight, relative organ weights. No apparent marked changes in the histopathology of the liver and kidney were detected. Data demonstrated that iARE induced in vitro cytotoxic effects in cancer cells are associated with lackof invivo toxicity. Thus, iARE was suggested to be considered as apotential therapeutic candidate for cancer treatment.